Green-derived 3D-printed photocatalytic reactors (3D-PCRs): Design strategies, integration, performance optimization, and sustainability perspectives - Hussain, Rabia Tasaduq; Anandapadmanaban, Baala H.; Lin, Chi-Wen; Liu, Shu-Hui; Jun Haslinda, Shariffuddin (Elsevier, 2026)
Photocatalysis has emerged as a promising and sustainable technology for environmental remediation and energy-related applications, including wastewater treatment, air pollution control, and solar-driven chemical conversion. Recent research efforts have increasingly focused on the development of green-derived photocatalysts synthesized from bio-waste, plant extracts, and agricultural residues, aiming to reduce environmental burdens while enhancing surface reactivity and charge transfer efficiency. In parallel, advances in additive manufacturing, particularly 3D printing, have enabled the fabrication of photocatalytic reactors with precisely engineered geometries, offering improved control over light distribution, mass transport, and catalyst immobilization. This review critically evaluates recent progress in integrating eco-friendly photocatalysts with 3D-printed reactor platforms, encompassing monolithic structures, microchannel designs, and LED-assisted configurations. Emphasis is placed on how reactor architecture influences photocatalytic performance, scalability, and operational efficiency. Key challenges, including material–reactor compatibility, long-term stability, reproducibility, and economic feasibility, are systematically discussed. Furthermore, strategies to enhance catalyst durability, reusability, and process robustness are highlighted. By identifying current limitations and research gaps, this review underscores the potential of combining green photocatalysts with 3D-printed reactor technologies as a viable pathway to scalable, cost-effective, and sustainable solutions for pollutant remediation and future clean energy applications.